2016
DOI: 10.1007/s10620-016-4091-8
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Clarithromycin Resistance and Treatment Failure Are Common in the USA

Abstract: H. pylori clarithromycin resistance in the USA exceeds the estimated 20 % prevalence compatible with successful empiric antibiotic therapy. This resistance resulted in a significant rate of treatment failure in all sites surveyed. Empiric therapy in the USA should be used with caution until there is better regional or local determination of H. pylori antibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…In this study, the mutations of 23S rRNA gene were found in 39.7%, mainly present at position 2143 (36.1%) with substitution A2143G and at a lesser extent at position 2142 (3.6%) with substitution A2142G. These results were consistent with data obtained from other authors from studies conducted in Iran in 2011 (the rate of clarithromycin resistance was 31.7%, all of them had A2143G mutation detected using PCR-RFLP) [16] and more recently in USA in 2016 (clarithromycinresistant H. pylori was common and observed in 32.3 % of cases; the specific variants A2142G and A2143G were detected using DNA sequencing) [17]. However, the rates of A2142G and A2143G mutation in our study were significantly higher than those reported from a study conducted in Malaysia in 2010 (only one sample with A2142G mutation and two samples with A2143G mutation were found among 105 samples, accounted for only 2.9%) [18], but significantly lower than the one in Yamade's study conducted in Japan (the mutation rate was 55.6% including 82 samples with A2143G mutation and 3 samples with A2142G) [19].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the mutations of 23S rRNA gene were found in 39.7%, mainly present at position 2143 (36.1%) with substitution A2143G and at a lesser extent at position 2142 (3.6%) with substitution A2142G. These results were consistent with data obtained from other authors from studies conducted in Iran in 2011 (the rate of clarithromycin resistance was 31.7%, all of them had A2143G mutation detected using PCR-RFLP) [16] and more recently in USA in 2016 (clarithromycinresistant H. pylori was common and observed in 32.3 % of cases; the specific variants A2142G and A2143G were detected using DNA sequencing) [17]. However, the rates of A2142G and A2143G mutation in our study were significantly higher than those reported from a study conducted in Malaysia in 2010 (only one sample with A2142G mutation and two samples with A2143G mutation were found among 105 samples, accounted for only 2.9%) [18], but significantly lower than the one in Yamade's study conducted in Japan (the mutation rate was 55.6% including 82 samples with A2143G mutation and 3 samples with A2142G) [19].…”
Section: Discussionsupporting
confidence: 90%
“…Other studies described a prevalence rate of 30-40 % in US adults and a 60-70 % infection rates in immigrant populations and those of lower socioeconomic status and living under crowded circumstances [3,4]. Resistance to clarithromycin, one of the components of recommended first-line therapy, has been increasing, with 10-15 % resistance in 2004 [5] and *30 % resistance reported in the article by Park et al [6] in this issue of Digestive Diseases and Sciences. Given that 320,000,000 people live in the USA, the number of persons infected with clarithromycin-resistant H. pylori is estimated in the hundreds of thousands, similar or greater than the estimated annual infections by carbapenem-resistant or b-lactamase-producing Enterobacteriaceae (35,300), drugresistant Campylobacter (310,000), or vancomycin-resistant Enterococcus (20,000) [1].…”
Section: Background and Significancementioning
confidence: 99%
“…One clear message highlighted by Park et al [6] is that the current rate of clarithromycin resistance for H. pylori in the USA exceeds the rate at which empiric therapy is recommended, yet empiric therapy is the standard treatment for H. pylori gastritis. The authors report a [20 % rate of clarithromycin-resistant H. pylori gastric infection, identified through genetic sequencing of H. pylori DNA extracted from paraffin-embedded tissue sections submitted from four locations across the USA.…”
Section: How the Article Addresses The Controversiesmentioning
confidence: 99%
“…The subsequent H. pylori Antimicrobial Resistance Monitoring Program (HARP) study, which included 347 clinical H. pylori isolates collected from 1998 to 2002 (Duck et al, 2004), reported rates of clarithromycin, metronidazole, and amoxicillin resistance of 12.9, 25.1, and 0.9%, respectively. Recently, a multicenter, retrospective cohort study was conducted in different geographic regions in the USA regarding H. pylori clarithromycin resistance, and the overall prevalence of clarithromycin resistance was 31.3% (Park et al, 2016). The increasing trend of clarithromycin resistance was thus confirmed in the USA.…”
Section: Helicobacter Pylori Recurrencementioning
confidence: 99%